2019
DOI: 10.1371/journal.pone.0211131
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of coronary artery disease and stroke and associated risk factors in Gaza community –Palestine

Abstract: Aim of studyTo determine the prevalence of cardiovascular disease and associated risk factors in the population of Gaza strip in Palestine.MethodsA cross-sectional stratified cluster sample design was applied in this study. A sample of 2240 participant (1121 males and 1119 females) aged ≥25 years participated in the study. For each individual, trained staff administered a questionnaire, where all variables of interest followed WHO’s STEP wise approach to surveillance chronic disease risk factors (STEPS) (WHO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 28 publications
2
43
1
Order By: Relevance
“…The incidence of stroke in our study is consistent with the two hospital-based studies conducted in North Palestine in 2008 and 2009 [7,8]. While the third study in 2019 was conducted in the Gaza strip and showed that the stroke has a lower incidence in this area [9]. Knowledge of stroke risk factors is known to reduce the incidence of stroke.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of stroke in our study is consistent with the two hospital-based studies conducted in North Palestine in 2008 and 2009 [7,8]. While the third study in 2019 was conducted in the Gaza strip and showed that the stroke has a lower incidence in this area [9]. Knowledge of stroke risk factors is known to reduce the incidence of stroke.…”
Section: Discussionsupporting
confidence: 89%
“…19 The female predominance is not surprising in our study and could be explained by the fact of high and rising frequency of obesity, diabetes and hypertension in our community, mainly in females. 20 The relationship between the elevated prevalence of MetS in women and android fat distribution and the predominant menopausal components was not analyzed. These factors may contribute to the results.…”
Section: Discussionmentioning
confidence: 99%
“…All appropriate patients suffering from acute STEMI presenting to Emergency Room was offered PPCI considering it as a gold standard treatment as well as thrombolysis with all pros and cons to educate and help them opt a better option for them. Candidates in acute STEMI for PPCI were as follows 1 . ST segment elevation on ECG with >1mm in two or more contiguous limb leads or >2mm in two or more contiguous precordial leads 7.2. presented with typical chest pain <12 hours without a previous history of thrombolytic therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Other inclusion factors involve participants with positive Allen`s sign for transradial Primary Percutaneous intervention (TR-PCI). Exclusion criteria for this study was 1 . STEMI Patients contraindicated candidates for PPCI 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation